ANALYSIS OF CONTACT STRESSES OF GEARS ON METAL CUTTING MACHINES - Prof. K.A. Karimov; Prof. I.P. Egamberdiev; Assistant Professor Sh. N. Yakhshiev; Chief Engineer K.S. Abdullaev; Assistant A. J. Mamadiyarov (Scholars Digest Publishing, 2024)
The contact stress in the mating wheels is a key parameter in gear design. This article presents an analysis of the contact stresses of a pair of spur gears as the second gear in the gearbox of the NT – 250M lathe in order to determine the maximum stress in the gear teeth. The contact stresses obtained from the theoretical values of the Hertz equation are compared with the finite element analysis method. Spur gears are modeled and assembled in SolidWorks V20 software and executed using ANSYS V21 software.
Keywords: Contact stress, ANSYS, spur gear, Hertz equation, power, torque, speed.